CASE STUDY OF DRY PACK MORTAR MANUFACTURE DESIGN IN AZOV DISTRICT OF ROSTOV REGION: IMPACT ASSESSMENT ON ENVIRONMENT - Sergey P. Danko; Larisa A. Zolotareva; Tatiana N. Savuskan; Tatyana B. Gavrilenko (Advanced Engineering Research)
The environmental management through designing an enterprise is described. A general ecological situation on the construction site and pollution sources is characterized. Design choices on depollution are the following: to use pneumotransport for cement, gypsum and lime handling, and to apply open air dry cleaning of cyclones and filters for open air purification.